(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
On the internet, nothing is immune. There is usually some element of surprise in cybercrime. Every person who uses the internet leaves traces of their online activity behind. The user can be located using these footprints. All of these might be gathered and utilized as digital evidence. Electronic evidence is a topic that is frequently discussed in India. However, Indian courts have always made an effort to make the legal situation clear, including the gathering procedure, admissibility, veracity, and relevance of electronic evidence. Few parts were still unclear, though. The purpose of this study is to describe the import of electronic evidence’s admissibility and veracity from an Indian legal standpoint. Additionally, to examine the legislative actions made by the Indian Parliament and the rulings issued about electronic evidence by the Hon’ble Supreme Court of India. This essay examines the issue of when an electronic evidence certificate is necessary, what information should be included in such a certificate, which is qualified to provide such a certificate, and at what point it is needed. This study also tries to determine whether or not spoken testimony regarding the content of electronic evidence can be provided.